Liquidity Traps, Learning and Stagnation - George W. Evans; Eran Guse; Seppo Honkapohja (Kiel Institute for the World Economy (IfW), 2007)
We examine global economic dynamics under learning in a New Keynesian model in which the interest-rate rule is subject to the zero lower bound. Under normal monetary and fiscal policy, the intended steady state is locally but not globally stable. Large pessimistic shocks to expectations can lead to deflationary spirals with falling prices and falling output. To avoid this outcome we recommend augmenting normal policies with aggressive monetary and fiscal policy that guarantee a lower bound on inflation. In contrast, policies geared toward ensuring an output lower bound are insufficient for avoiding deflationary spirals.
Keywords: E58; E52; E63; 330; Adaptive Learning; Monetary Policy; Fiscal Policy; Zero Interest Rate Lower Bound; Indeterminacy